THE EVALUATION OF STONE MASTIC ASPHALT MIXÃâÃâS PERFORMANCE USING SASOBIT MODIFIED ASPHALTÃâÃÂ® TOWARD FATIGUE FAILURE CRITERIA & PERMANENT DEFORMATION - HANA MARJA MANGGALA (NIM : 26912005), R.
It is important to have roads with strong pavement structure to support high traffic load, so that innovation in materials pavement design is needed to be produced. Today, flexible pavement have a variety of types, such as Stone Mastic Asphalt (SMA). SMA is considered to have advantages compared with other types of pavement because of SMA is more flexible, more durable, and more resistant to rutting. This study is intended to evaluate the performance of Stone Mastic Asphalt mixtures using Sasobit® modified asphalt toward fatigue failure criteria and permanent deformation. Three types of mixtures are prepared, namely: asphalt Pen 60/70 with 0,3% cellulose, asphalt Pen 60/70 with Sasobit® 3%, and asphalt Pen 60/70 with Sasobit® 4%. The physical properties of asphalt and aggregate are tested and compared with AASHTO specifications and British Standard. While the performance of the mixtures are obtained through Marshall Stability testing, Draindown, ITS, permanent deformation and fatigue crack using Four Point Bending Test. Addition of Sasobit® into asphalt Pen 60/70 raised rheological properties of asphalt. Marshall test results show that asphalt mixture modified with Sasobit® has the highest value of Marshall Stability. Draindown test results showed asphalt Pen 60/70 mixture with the addition of 0,3% cellulose fiber can prevent draindown compared to asphalt modified with Sasobit®. ITS test results produce TSR value are varied, which mix with asphalt modified with Sasobit® 4% has the highest value. Wheel Tracking Test results on asphalt modified with Sasobit® has the smallest deformation value than the asphalt without Sasobit®. While fatigue testing showed values varied, where the highest resistance to fatigue is a mixture of asphalt modified with Sasobit® 4%. In general, the addition Sasobit® in asphalt modification can lower the temperature of mixing and compaction and to improve the rheological properties of asphalt. The positive effects of asphalt modified with Sasobit® in SMA mixture can be used to improve the performance of the mixture.